Left atrial volume and function in patients with Behcet's disease assessed by real-time three-dimensional echocardiography - Akturk, Erdal; Yagmur, Julide; Kurtoglu, Ertugrul; Ermis, Necip; Acikgoz, Nusret; Sener, Serpil; Ozdemir, Ramazan (Oxford Univ Press, 2012)
Aims Behcet's disease (BD), a multisystemic inflammatory disorder, has been associated with a number of cardiovascular dysfunctions, including endomyocardial fibrosis of the right heart, atrial fibrillation, ventricular arrhythmias and sudden cardiac death. The incidence and nature of cardiac involvement in BD are not yet clearly documented. Our aim was to evaluate left atrial (LA) volume and functions using real-time three-dimensional echocardiography (RT3DE) in Behcet's patients without any cardiac symptom. Methods end results The study included 40 BD (16 females, 24 males and mean age of 33 +/- 7 years) and 30 healthy (11 females, 19 males and mean age of 35 +/- 6 years) subjects. All the patients' demographic parameters such as age, gender, and duration of BD were recorded. All the individuals underwent comprehensive 2D echocardiography examination, and RT3DE was performed to assess LA volumes and mechanical functions. LA maximum volume (V-max) and before atrial contraction volume (V, re A) LA active stroke volume and total stroke volumes (TSV), total emptying and active emptying fractions and expansion index were significantly higher in Behcet's disease patients when compared with the controls (P < 0.0001 for all). LA passive emptying fraction was significantly lower in the patients with BD than in the controls (41 +/- 7 vs. 44 +/- 5, P = 0.039). There were positive correlations between TSV and high-sensitive C-reactive protein level (r = 0.413, P = 0.008), TSV, and disease duration (r = 0.417, P < 0.007). Conclusion Our study has shown that LA mechanical functions and volumes are impaired in BD. These results may be an early form of subclinical cardiac involvement in patients with BD who have no clinical evidence for cardiovascular disease.
Keywords: Behcet's disease; left atrial volume; left atrial function; real-time three-dimensional echocardiography